KONSEP KESELAMATAN MASYARAKAT KAWASAN ADAT KAJANG DALAM TRADISI ANGNGANRO ( ANALISIS URF’) - Laman, Ilham; Widyani, Sri (Citra Media Publishing, 2023)
This article discusses the Angnganro Tradition in the Community of Kajang District, Bulukumba Regency from the Perspective of Islamic Law. The type of research is qualitative field research, with a legal sociology research approach. Legal sociology approach, namely the approach used to find out how the facts that occur in the field are related to the traditions of the local community. The results of this study indicate that the angnganro tradition is a ceremony of releasing vows or a ceremony of giving thanks because one's prayers and requests have been answered. For example, a person is affected by a disaster or a dangerous disease and then he prays that if he is safe from harm or recovers from his illness, he will carry out the